Astragaloside IV as a promising therapeutic agent for liver diseases: current landscape and future perspectives - Chen, Chunyan; Bu, Xiaolan; Deng, Liping; Xia, Jiayan; Wang, Xinming; Chen, Li; Li, Wen; Huang, Jie; Chen, Qixiang; Wang, Cheng (Frontiers in Pharmacology, 2025)
Astragaloside IV (C41H68O14, AS-IV) is a naturally occurring saponin isolated from the root of Astragalus membranaceus, a widely used traditional Chinese botanical drug in medicine. In recent years, AS-IV has attracted considerable attention for its hepatoprotective properties, which are attributed to its low toxicity as well as its anti-inflammatory, antioxidant and antitumour effects. Numerous preclinical studies have demonstrated its potential in the prevention and treatment of various liver diseases, including multifactorial liver injury, metabolic-associated fatty liver disease, liver fibrosis and liver cancer. Given the promising hepatoprotective potential of AS-IV and the growing interest in its research, this review provides a comprehensive summary of the current state of research on the hepatoprotective effects of AS-IV, based on literature available in databases such as CNKI, PubMed, ScienceDirect, Google Scholar and Web of Science. The hepatoprotective mechanisms of AS-IV are multifaceted, encompassing the inhibition of inflammatory responses, reduction of oxidative stress, improvement of insulin and leptin resistance, modulation of the gut microbiota, suppression of hepatocellular carcinoma cell proliferation and induction of tumour cell apoptosis. Notably, key molecular pathways involved in these effects include Nrf2/HO-1, NF-κB, NLRP3/Caspase-1, JNK/c-Jun/AP-1, PPARα/FSP1 and Akt/GSK-3β/β-catenin. Toxicity studies indicate that AS-IV has a high level of safety. In addition, this review discusses the sources, physicochemical properties, and current challenges in the development and clinical application of AS-IV, providing valuable insights into its potential as a hepatoprotective agent in the pharmaceutical and nutraceutical industries.